Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Menggunakan Jasa Pegadaian Pada Kantor Pegadaian Syariah Kota Tidore Kepulauan - Kahar, Bayu Sanjaya (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine whether promotion factors, personal factors, and service quality can influence customer decisions to use Islamic pawnshop services in Tidore Islands City. The type of research used in this study is quantitative research. This study describes the factors that influence customer decisions to use Islamic pawnshop services. The sampling technique used is non-probability sampling because the population is unknown. The data used are primary data and secondary data collected through questionnaires. Data analysis uses descriptive statistical analysis, research instrument analysis, and multiple linear regression analysis and the data is processed using SPSS version 20. The results of this study indicate that (1) individually the promotion variable has an effect and is significant on customer decisions (2) personal factor variables do not have a significant effect on customer decisions (3) service quality variables do not have a significant effect on customer decisions (4) Simultaneously the promotion, personal, and service quality variables do not have a significant effect on customer decisions.